Numerical Simulation of Dynamic Characteristics of Dam Concrete Based on Fuzzy Set - Fang Jianyin; Liu Ke; Dang Faning; Li Shutian (Geofluids)
The dynamic characteristics of concrete are the key point of the dam seismic safety design. In order to study the dynamic characteristics of concrete, a CT scan test of concrete under dynamic load was carried out; CT scan images of the concrete loading process were obtained. Based on the definition of integrity, integrity area, and intercepted sections in the quantitative zoning theory, the concrete CT images were divided into the hole or crack area (P0−λ1), hardened cement stone area (Pλ1−λ2), and aggregate area (Pλ2−1). And the determination method of partition threshold is studied. Then, based on the CT resolution unit, a concrete numerical calculation model of structural random is established, and the numerical simulation experiment of concrete under uniaxial dynamic load is carried out. The results show that the concrete numerical calculation model of structural random is very close to the actual mesostructure of concrete, and the interface thickness between aggregate and hardened cement is very close to the actual interface thickness (which is 40~50 μm). Under the action of dynamic load, the damage of the sample is mainly concentrated in the upper part of the sample, and the damage is easy to occur at the initial defect place, and the damage occurs at multiple points at the same time. The damage crack is relatively straight, the phenomenon of the crack passing through the aggregate is obvious, and the crack expands along the fastest path of energy release.